Two-phase photobleaching dequenching in dye-loaded liposomes - Lee, Elizabeth Mei Yin (2014)
In this study, dye-loaded liposomes were characterized and exposed to laser excitation for a prolonged duration to assess their suitability as biological random lasing agents. The liposomes were fabricated using a modified reverse phase evaporation method and encapsulates carboxyfluorescein dye at self-quenched concentrations. At high liposome concentrations, the fluorescence spectra exhibited two peculiar peaking events over time under 405nm laser excitation. The two peculiar peaking events were denoted as the primary and secondary dequenching, and was theorized to be caused by photobleaching-induced reduced self-quenching effects; hence, the name dequenching. The mechanism of the primary dequenching was attributed to the photobleaching of outermost dye molecules which subsequently stop participating in self-quenching. The secondary dequenching was attributed to the anomalous diffusion of the dye molecules into the liposomal core causing further dequenching. The results of this study show the potential of optically tuning the fluorescence properties of dye-loaded liposomes using a continuous-wave laser and also provide insight to further explore the use of liposomes as an organic random lasing agent.